RASIO BUAH JAMBU BIJI MERAH (Psidium guajava L.) DAN BUAH APEL HIJAU MANALAGI (Mallus sylvestris Mill.) TERHADAP MUTU PERMEN JELLY - Sahputra, Muhammad Bijaksono; Hamzah, Faizah; Johan, Vonny Setiaries (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was to obtain the best ratio of red guava and green apple manalagi in making of jelly candy. This research used Complete Randomized Design (CRD) with five treatments and three replications followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatments in this research were P1 (ratio of red guava and green apple manalagi 90 : 10), P2 (ratio of red guava and green apple manalagi 80 : 20), P3 (ratio of red guava and green apple manalagi 70 : 30), P4 (ratio of red guava and green apple manalagi 60 : 40) and P5 (ratio of red guava and green apple manalagi 50 : 50). The result of analysis of variance showed that ratio of red guava and green apple manalagi has significantly affected the moisture contents, ash contents, vitamin C, reduction sugar contents, descriptive of sensory test on colour, flavour, texture, hedonic of sensory on texture and overall test, but did not significantly affected hedonic sensory of the colour, flavour and taste of jelly candy. The best formulation of jelly candy was P1 (ratio of red guava and green apple manalagi 90 : 10), with moisture content 9.48%, ash content 0.51%, vitamin C 66.29%, sugar reduction content 19.60%. Hedonic score of P1 were 2.40% (colour), 2.97% (taste), 2.20% (flavour), 2.63% (texture) and 3.06% (rather like on overall test). Keywords: jelly candy, red guava, green apple manalagi